Single Case Study on the Effectiveness of Macquarie Injury Management Group (MIMG) Protocol on the Subject of Primary Osteoarthritis of Knee - Ansupriya Neog; Ankur Jyoti Bora; Prasenjit Bhattacharyya (International Journal of Orthopedic Nursing and Practices, 2025)
Aim: To check the effectiveness of Macquarie Injury Management Group (MIMG) protocol in subject of primary osteoarthritis of knee. Purpose: Manual therapy has been shown to be an effective treatment for knee osteoarthritis, but it is necessary to evaluate the effectiveness of the MIMG manual therapy technique. However, there is a dearth of literature on the effectiveness of Macquarie injury management group (MIMG) protocol in subject of osteoarthritis of knee. Methodology: This is a single case study where a patient with grade II of primary osteoarthritis of knee reported to the OPD of Jorhat Medical College and Hospital. MIMG techniques were performed on the patient’s affected knee under constant guidance for three alternate days a week for 2 weeks. Baseline measures of VAS for pain goniometry for ROM and KOOS for functional independence were taken on day 0, 7th and 14th day. Results: Data was gathered before and after treatment, and the values were analyzed using SPSS software. It was seen that VAS decreased from 7 to 3 on the last day, range of motion for flexion and extension also showed gradual increase and functional independence using KOOS (Knee Injury and Osteoarthritis Outcome Score) came from 43 to 76 at the end of the study period. Conclusion: From this case study we believe that the protocol outlined in this research demonstrated significant improvement in ROM and reducing pain and increase in functional independence in a subject with knee osteoarthritis and additional treatment options need to be explored and studied further.
Keywords: Macquarie injury management group protocol; Osteoarthritis of knee; knee injury and osteoarthritis outcome score